2015
DOI: 10.1111/jipb.12366
|View full text |Cite
|
Sign up to set email alerts
|

Role of rice cytosolic hexokinase OsHXK7 in sugar signaling and metabolism

Abstract: We characterized the function of the rice cytosolic hexokinase OsHXK7 (Oryza sativa Hexokinase7), which is highly upregulated when seeds germinate under O2 -deficient conditions. According to transient expression assays that used the promoter:luciferase fusion construct, OsHXK7 enhanced the glucose (Glc)-dependent repression of a rice α-amylase gene (RAmy3D) in the mesophyll protoplasts of maize, but its catalytically inactive mutant alleles did not. Consistently, the expression of OsHXK7, but not its catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…Sucrose synthase 3 ( OsSUS3 ) was down-regulated at the meiotic stage and up-regulated at the single microspore stage, and OsSUS2 was up-regulated at the single microspore stage. In addition, hexokinase genes have a great influence on the plant sugar signalling pathway (Cho et al 2006 , 2009 ; Kim et al 2016 ). The hexokinase 10 ( OsHXK10 ) plays a vital role in pollen germination, anther dehiscence, and hence grain filling in rice (Xu et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose synthase 3 ( OsSUS3 ) was down-regulated at the meiotic stage and up-regulated at the single microspore stage, and OsSUS2 was up-regulated at the single microspore stage. In addition, hexokinase genes have a great influence on the plant sugar signalling pathway (Cho et al 2006 , 2009 ; Kim et al 2016 ). The hexokinase 10 ( OsHXK10 ) plays a vital role in pollen germination, anther dehiscence, and hence grain filling in rice (Xu et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings, together with the function of SnRK1 for germination under starvation (Lu et al, 2007), are consistent with starvation signals being required for starch mobilization during anaerobic germination and an antagonistic function of T6P and SnRK1. Coleoptile length during germination at low oxygen was decreased in rice hexokinase (HXK7) mutants but increased in overexpressors (Kim et al, 2016). The authors suggest that HXK7 fuels anaerobic fermentation and that its catalytic function rather than its role in sugar signaling is responsible for anaerobic germination tolerance.…”
Section: Germination and Cotyledon Greeningmentioning
confidence: 90%
“…Recently, Cheng et al (2011) identified that OsHXK1, 7, and 8 in O. sativa are located in the cytoplasm and nucleus, since they lack the plastidic transit peptide and the membrane anchor domain; thus, these enzymes are classified as type-C HXKs [10]. The variety and multiple subcellular localizations of HXKs indicate that these proteins may have functions in various physiological processes of plants, such as anther dehiscence, pollen germination [11], stomatal closure [12], germination [13], programmed cell death [14], and responses to abiotic or biotic stresses [15]. It has been identified that HXKs have important roles in sugar metabolism and sugar signaling [7,16].…”
Section: Introductionmentioning
confidence: 99%